Diet of the 21st-century person — food intolerances and elimination diets - Gacoń, Ewa (Health Promotion & Physical Activity, 2023)
In a dynamically changing world and environment, the human diet is subject to numerous changes, as well as the quality of selected products. More and more often, patients who report gastrointestinal complaints after eating certain foods come to doctors. This situation often ends with the introduction of an elimination diet, which conducted without the supervision of a specialist, can have various negative effects. The work aims to present the latest results of research on the diet of modern man, published in international journals, available in the PubMed database and the Google Schoolar. The review discusses the most common food intolerances, their mechanisms and treatment options with particular emphasis on therapy with elimination diets and their potential health consequences. The discussed health problems are related to environmental changes and at the same time, significantly reduce the quality of life of people struggling with them.